Features of the Labor Market of the Republic of Uzbekistan - Iskandarov B. A. (International Journal on Orange Technologies, 2022)
This article discusses the national labor market and its features, provides statistical data on the structure of the labor market, presents a program to increase the level of employment of the population during the period of economic recovery after the pandemic